Fusarium biocontrol: antagonism and mycotoxin elimination by lactic acid bacteria - Krishnan, S. Vipin; Nampoothiri, K. Madhavan; Suresh, Anandhu; Linh, Nguyen Thuy; Balakumaran, P. A.; Pócsi, István; Pusztahelyi, Tünde (Frontiers in Microbiology, 2024)
Mycotoxins produced by Fusarium species are secondary metabolites with low molecular weight formed by filamentous fungi generally resistant to different environmental factors and, therefore, undergo slow degradation. Contamination by Fusarium mycotoxins in cereals and millets is the foremost quality challenge the food and feed industry faces across the globe. Several types of chemical preservatives are employed in the mitigation process of these mycotoxins, and they help in long-term storage; however, chemical preservatives can be used only to some extent, so the complete elimination of toxins from foods is still a herculean task. The growing demand for green-labeled food drives to evade the use of chemicals in the production processes is getting much demand. Thus, the biocontrol of food toxins is important in the developing food sector. Fusarium mycotoxins are world-spread contaminants naturally occurring in commodities, food, and feed. The major mycotoxins Fusarium species produce are deoxynivalenol, fumonisins, zearalenone, and T2/HT2 toxins. Lactic acid bacteria (LAB), considered safe (GRAS), is a well-explored bacterial community in food preparations and preservation for ages. Recent research suggests that LAB are the best choice for extenuating Fusarium mycotoxins. Apart from Fusarium mycotoxins, this review focuses on the latest studies on the mechanisms of how LAB effectively detoxify and remove these mycotoxins through their various bioactive molecules and background information of these molecules.